1992
DOI: 10.1128/iai.60.9.3475-3479.1992
|View full text |Cite
|
Sign up to set email alerts
|

The Th1/Th2-like switch in syphilitic infection: is it detrimental?

Abstract: Organisms that cause chronic diseases have evolved mechanisms to evade those immune defenses that resolve the acute stage of infection (10, 12-14, 21, 22, 32, 35, 37, 38, 40, 42, 45-49, 53). Much is to be learned by specifically identifying the mechanisms underlying these evasive strategies. Important new insights will emerge in terms of immunoregulatory pathways. This in turn will facilitate vaccine development. A good example is leishmania infection. The acute stage of this disease is resolved by DTH-macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…The result of this report indicated additionally that Th2 lymphocytes are able to produce cytokines early in the disease, when Th1 lymphocytes weakly produce cytokines and in early latent syphilis in which for many years syphilis remains latent. Fitzgerald [38] hypothesized that Th1 response is dominant in primary syphilis and then shifts to Th2 as the disease progresses to the secondary stage. The results of our work seem to indicate that such shift to Th2, which acts as a negative feedback mechanism to control and limit T cell activation, could occur in early latent syphilis when only IL-12 (not published) and IL-10 are secreted.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this report indicated additionally that Th2 lymphocytes are able to produce cytokines early in the disease, when Th1 lymphocytes weakly produce cytokines and in early latent syphilis in which for many years syphilis remains latent. Fitzgerald [38] hypothesized that Th1 response is dominant in primary syphilis and then shifts to Th2 as the disease progresses to the secondary stage. The results of our work seem to indicate that such shift to Th2, which acts as a negative feedback mechanism to control and limit T cell activation, could occur in early latent syphilis when only IL-12 (not published) and IL-10 are secreted.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the guinea‐pig model, a predominant Th2 immune response was observed as early as 3 days after infection. In the rabbit model, Fitzgerald 26 reported a switch from a Th1 [IL‐2, interferon‐γ (IFN‐γ)] to a Th2 response after 9–14 days of infection. Van Voorhis et al ., 27 using skin biopsies obtained from African patients with primary and secondary syphilis, suggested that the predominantly Th1 response (IL‐2, IL‐12 and IFN‐γ) seen in patients with primary syphilis must be responsible for the effective clearance of the pathogen from the site of infection and dissolution of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have suggested that chronic infection with various bacterial, viral, and parasitic agents involves a cytokine switch from a Th1 to a Th2 immune response (234)(235)(236)(237). Although this model might represent an oversimplification of the immune response (238), the establishment of persistence can be schematically described as two distinct phases, characterized by a different balance of Th1/Th2 responses (Fig.…”
Section: The Host Immune Response To Salmonella Persistencementioning
confidence: 99%